The School Health Index as an Impetus for Change - Lisa K. Staten, PhD; Nicolette I. Teufel-Shone, PhD; Victoria E. Steinfelt, MS; Nohemi Ortega; Karen Halverson; Carmen Flores; Michael D. Lebowitz, PhD (Centers for Disease Control and Prevention, 2005)
Background The increase in childhood obesity and prevalence of chronic disease risk factors demonstrate the importance of creating healthy school environments. As part of the Border Health Strategic Initiative, the School Health Index was implemented in public schools in two counties along the Arizona, United States-Sonora, Mexico border. Developed in 2000 by the Centers for Disease Control and Prevention, the School Health Index offers a guide to assist schools in evaluating and improving opportunities for physical activity and good nutrition for their students. Context Between 2000 and 2003, a total of 13 schools from five school districts in two counties participated in the School Health Index project despite academic pressures and limited resources. Methods The Border Health Strategic Initiative supported the hiring and training of an external coordinator in each county who was not part of the school system but who was an employee in an established community-based organization. The coordinators worked with the schools to implement the School Health Index, to develop action plans, and to monitor progress toward these goals. Consequences The School Health Index process and school team participation varied from school to school. Individual plans were different but all focused on reducing in-school access to unhealthy foods, identified as high-fat and/or of low nutritional value. Ideas for acting on this focus ranged from changing the content of school lunches to discontinuing the use of nonnutritious foods as classroom rewards. All plans included recommendations that could be implemented immediately as well as those that would require planning and perhaps the formation and assistance of a subcommittee (e.g., for developing or adopting a district-wide health curriculum). Interpretation After working with the School Health Index, most schools made at least one immediate change in their school environments. The external coordinator was essential to keeping the School Health Index results and action plans on the agendas of school administrators, especially during periods of staff turnover. Staff turnover, lack of time, and limited resources resulted in few schools achieving longer-term policy changes.